Representation of cultural identity of the Dayak Ngaju community (structural dynamic study) - Misnawati Misnawati; Petrus Poerwadi; Anwarsani Anwarsani; Alifiah Nurachmana; Diplan Diplan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The purpose of this study is to describe what cultural identity is revealed through the oral literature of the Dayak Ngaju people. This research uses a qualitative approach. Data collection techniques in this study use: (1) recording techniques, both audio and audiovisual, (2) recording, (3) in-depth interviews, (4) literature study and documentation analysis. The main data source analyzed is the deder text in Rakumpit Subdistrict, Bukit Liti, and Palangka Raya City, Central Kalimantan. The examination of the validity of the data in this qualitative study follows that suggested by Lincoln and Gube, covering four techniques: credibility, transferability, dependability, and confirmability. The data collected was analyzed using the Dynamic Structural Theory. Dynamic Structural Theory is used methodologically to analyze the research problem formulation. Ngaju Dayak community research findings that can be identified from the analyzed are (1) hapakat, (2) friendly and polite, (3) harmonious and tolerant, (4) religious, (5) respect for ancestors, (6) isen mulang, and (7) menteng.